2021
DOI: 10.3390/coatings11101229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Voltage Sags on the Continuity of the Operation and Lifespan of Single-Phase Industrial Robots

Abstract: Due to the increase in the number of automated processes that employ industrial robots (especially in industrial and laboratory environments, including vacuum systems), and the resulting increase in the number of unresolved service requests, the purpose of the authors’ research was to confirm the occurrence of disturbances in the form of voltage sags that are not recorded by automation systems and which lead to the destruction of robots or their equipment in areas defined by the characteristics of ITIC/SEMI F4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, in a previous study [18], the authors tested the effect of voltage sags on single-phase industrial robots and were able to verify that there are states that lead to receiver damage in an area they called "A" within the "no damage region" shown in Fig- ure 2. Those disturbances damaged the controller.…”
Section: Measurement System and Methodologymentioning
confidence: 99%
“…However, in a previous study [18], the authors tested the effect of voltage sags on single-phase industrial robots and were able to verify that there are states that lead to receiver damage in an area they called "A" within the "no damage region" shown in Fig- ure 2. Those disturbances damaged the controller.…”
Section: Measurement System and Methodologymentioning
confidence: 99%
“…The flux surface is chosen as follows: 𝑆 𝜑𝑖 = 𝜑 𝑖 𝑟𝑒𝑓 − 𝜑 𝑖 and the derivative of the surface is given by: 𝑆 ̇𝜑𝑖 = 𝜑̇𝑖 𝑟𝑒𝑓 − 𝜑̇𝑖. During the sliding mode and in permanent regime, 𝑆 ̇𝜑𝑖 = 0 , 𝑆 𝜑𝑖 = 0 and 𝑖 𝑠𝑑𝑖_𝑛 𝑟𝑒𝑓 = 0, the equivalent control can be given as (9).…”
Section: Rotor Flux Controllermentioning
confidence: 99%
“…Voltage-dips which are responsible for the majority of these  ISSN: 2088-8694 disturbances, are primarily caused by the start-up of large driving loads and power system faults such as lightning. Because these faults can never be eliminated in the electrical system, we must design equipment that can withstand the most common voltage dips [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research by Wagner et al [6], a case study on the monitoring of disturbances related to power quality revealed that 68% of recorded disturbances are voltage sags and that they represent the main cause of production shutdowns and losses. The above problems, as well as the increasing incidence of misdiagnosed faulty conditions in industrial robots (service requests based on incorrect logging of a disturbance source), are presented in a study on the influence of voltage dips on the continuity of operation and the life span of single-phase industrial robots [7]. In fact, as technology has improved and more power electronics devices have been used, the equipment used in industrial systems has become more sensitive to these kinds of things [8].…”
Section: Introductionmentioning
confidence: 99%